Oxford Textbook of Paediatric Pain 2013
DOI: 10.1093/med/9780199642656.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Psychological theories and biopsychosocial models in paediatric pain

Abstract: The purpose of this chapter is to review existing biopsychosocial models of paediatric pain and to examine common key factors across different theoretical conceptualizations. Critical gaps in the empirical and theoretical literature are elucidated. In particular, lack of specific attention to developmental factors in biological, behavioural, and social functioning and the need for models that examine gaps in different types of pain responding (e.g. immediate acute pain response, acute pain responding in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…Much more than a simple noxious stimulus leading to an individual’s sensory experience, the experience of pain also involves a host of other features including biological, psychological, social, and contextual factors 39 41 (see also Fig. 1 which is consistent with the cited models).…”
Section: Vaccination: a Painful And Fear-inducing Experiencesupporting
confidence: 71%
See 1 more Smart Citation
“…Much more than a simple noxious stimulus leading to an individual’s sensory experience, the experience of pain also involves a host of other features including biological, psychological, social, and contextual factors 39 41 (see also Fig. 1 which is consistent with the cited models).…”
Section: Vaccination: a Painful And Fear-inducing Experiencesupporting
confidence: 71%
“…After many decades of research, the Gate Control Theory and biopsychosocial models of pain all clearly indicate that emotions shape one’s pain experience and expression 39 , 41 , 53 ; however, negative emotions regarding needle procedures such as vaccinations are often ignored. In the case of fear, this is particularly problematic, as fear seems to have a bidirectional relationship with pain.…”
Section: Vaccination: a Painful And Fear-inducing Experiencementioning
confidence: 99%
“…While two studies identified significant relationships between proximal soothing behaviors, such as rocking and holding, and infant pain-related distress [ 6 , 8 ], other studies found that, after controlling for infant distress prior to and immediately following the vaccination needle, the contribution of proximal soothing behaviors to pain outcomes was minimal [ 10 , 12 ]. However, in line with previous theory [ 6 , 7 ], proximal soothing behaviors typically account for more of the variance in distress regulation, as opposed to distress reactivity [ 6 , 10 ].…”
Section: Introductionsupporting
confidence: 70%
“…This paradigm has unique benefits as it offers a naturalistic, ethical, and universally standardized setting in which children’s pain-related distress regulation capacity can be observed in the context of parent behaviors. Infants’ behavior in response to a painful stimulus was conceptualized as involving two distinct, yet interrelated phases: the infant’s immediate behavioral response following the painful stimulus (i.e., pain-related distress reactivity), and the more distal or non-immediate behavioral response (i.e., pain-related distress regulation) [ 6 , 7 ]. Infant behavior during the reactivity phase is largely driven by biological and genetic factors, in addition to previous pain experiences, whereas behavior during the regulation phase is more closely linked to broader contextual factors, such as parent pain-management behaviors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different potential factors relate to infant pain-related distress before the needle, immediately after the needle, and in the period that follows the peak distress after needle. 12 Accordingly, to characterize the impact of the intervention on pain-related distress, distress was analyzed separately for: (1) the preprocedure phase, which occurred postintervention but before vaccine injection(s); (2) the acute procedure phase (within the first minute of needle puncture and vaccine injection); and (3) the recovery procedure phase (1 to 5 min after vaccine injection(s). In addition, some idiosyncratic combinations of before needle, needle, and recovery phases were used by researchers and these were analyzed separately.…”
Section: Methodsmentioning
confidence: 99%